Energy and exergy analysis of the heat pump cycle using working fluids with low environmental impact - Dima, Daniel; Dobrovicescu, Alexandru; Dobre, Cătălina (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study presents the energetic and energetic analysis of the heat pump cycle, used for heating residential spaces. The heat pump is of the air-water type, taking heat at the level of the evaporator from the environment. The working fluids used are: R1233zd(E), R1234ze, R152a, R1234yf. Exergy analysis is used as a research tool. Based on the exergy analysis, the identification of malfunctions at the level of each device and process can be easily achieved. The study shows that the working fluid R1233zd(E) presents the highest coefficient of performance and the highest exergetic efficiency.